2004
DOI: 10.1530/rep.1.00282
|View full text |Cite|
|
Sign up to set email alerts
|

Localization and temporal regulation of tissue inhibitors of metalloproteinases 3 and 4 in bovine preovulatory follicles

Abstract: The matrix metalloproteinases (MMPs) and their tissue inhibitors (TIMPs) are potential regulators of the focalized extracellular matrix degradation required for ovulation. The objectives of the present study were to determine localization and temporal regulation of TIMP-3 and TIMP-4 mRNA and protein in bovine preovulatory follicles. Ovaries containing preovulatory follicles were collected at 0, 12 and 20 h after GnRH injection for real-time PCR quantification of TIMP-3 and TIMP-4 mRNAs and immunohistochemical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…In this previous study, staining intensity was highest in the theca interna and luteal cells. An elevated thecal expression of TIMP3 is also seen in other species, such as porcine [47], equine [48], and bovine [42]. This temporal progression of TIMP3 expression in the follicle may allow for the protection of the different cellular layers of the follicle from degradation by matrix metalloproteinases during specific phases of growth and maturation while ensuring the viability of those cells for luteinization as the corpus luteum forms.…”
Section: Timp3 During Human Ovulationmentioning
confidence: 93%
See 1 more Smart Citation
“…In this previous study, staining intensity was highest in the theca interna and luteal cells. An elevated thecal expression of TIMP3 is also seen in other species, such as porcine [47], equine [48], and bovine [42]. This temporal progression of TIMP3 expression in the follicle may allow for the protection of the different cellular layers of the follicle from degradation by matrix metalloproteinases during specific phases of growth and maturation while ensuring the viability of those cells for luteinization as the corpus luteum forms.…”
Section: Timp3 During Human Ovulationmentioning
confidence: 93%
“…increases approximately 2-fold at 12 h after GnRH injection [42]. Furthermore, it has been shown that TIMP3 mRNA is more abundant in healthy follicles [31,43]; thus, this rise in TIMP3 in the human, bovine, and rat may be required for the final stages of follicular maturation in preparation for the matrix remodeling that takes place before ovulation and expulsion of the oocyte.…”
Section: Timp3 During Human Ovulationmentioning
confidence: 99%
“…RNA isolation, RT, and quantitative real-time RT-PCR analysis were performed as described previously (40,41) using published primer sequences for aromatase and ␤-actin (41,42) and absolute quantification using standard curve technology. Standard curves for each gene were constructed using 10-fold serial dilutions of corresponding plasmids run on the same plates as samples.…”
Section: Rna Isolation Reverse Transcription (Rt) and Quantitative mentioning
confidence: 99%
“…TIMP-4 is a secreted protein expressed at low levels in the placenta (Greene et al, 1996;Leco et al, 1997). In recent years, to conform the role of TIMP-4, many studies were carried out to study its expression, results demonstrated that TIMP-4 was present in several malignant tumors and tumor cell lines (Tunuguntla et al, 2003;Zhao et al, 2004;Jiang et al, 2001;Zhang et al, 2002), as well as in the animal follicle and ovary (Riley et al, 2001;Li et al, 2004;Simpson et al, 2003). It also has been shown that TIMP-4 was expressed in human placenta, fetal membranes, decidua (Greene et al, 1996;Riley et al, 1999), and endometrium Pilka et al, 2004).…”
Section: Introductionmentioning
confidence: 99%